National approaches to cultural diplomacy : comparative case studies of China and Japan - Čadilová, Karolína (2025)
This thesis analyses the cultural diplomacy of China and Japan, focusing on the instruments and strategies they use in order to gain soft power. Using a comparative analysis of two case studies, it examines each country’s nation branding practices, national cultural institutes and supplementary cultural activities. The theoretical background situates cultural diplomacy within the soft power theory, outlining definitions and instruments of both. The findings show that, although China and Japan utilise similar cultural diplomacy instruments, their approaches differ markedly. Japan combines traditional and contemporary cultural resources, benefiting from globally appealing popular culture and a credible institutional actor in the Japan Foundation. China places greater emphasis on traditional culture and the extensive network of Confucius Institutes, but strong state control limits the perceived authenticity and effectiveness of its efforts.